Green‐Light‐Induced Inactivation of Receptor Signaling Using Cobalamin‐Binding Domains. Issue 16 (20th March 2017) - Kainrath, Stephanie; Stadler, Manuela; Reichhart, Eva; Distel, Martin; Janovjak, Harald
Abstract: Optogenetics and photopharmacology provide spatiotemporally precise control over protein interactions and protein function in cells and animals. Optogenetic methods that are sensitive to green light and can be used to break protein complexes are not broadly available but would enable multichromatic experiments with previously inaccessible biological targets. Herein, we repurposed cobalamin (vitamin B12) binding domains of bacterial CarH transcription factors for green‐light‐induced receptor dissociation. In cultured cells, we observed oligomerization‐induced cell signaling for the fibroblast growth factor receptor 1 fused to cobalamin‐binding domains in the dark that was rapidly eliminated upon illumination. In zebrafish embryos expressing fusion receptors, green light endowed control over aberrant fibroblast growth factor signaling during development. Green‐light‐induced domain dissociation and light‐inactivated receptors will critically expand the optogenetic toolbox for control of biological processes. Abstract : When green means stop : The fusion of a bacterial cobalamin (vitamin B12) binding domain (CBD) and a mammalian kinase domain (KD) results in constitutively active signaling in the dark. Signaling leads to developmental defects in zebrafish that can be avoided by green‐light illumination to permit normal development (AdoCbl=5′‐deoxyadenosylcobalamin, MYR=myristoylation membrane anchor).